Angusticopula rowlingiana, a new melosiroid diatom (Bacillariophyta) from Ascension Island (South Atlantic Ocean) - van De Vijver, Bart; Wilfert, Sandra; Houk, Vaclav; John, David M. (Phytotaxa, 2019)
During a diatom survey of some samples from Ascension Island, a remote island located in the southern Atlantic Ocean, an unknown melosiroid diatom species was studied using both light and scanning electron microscopy. It proved to be a new species described as Angusticopula rowlingiana sp. nov. and characterized by a large number of narrow copulae in the girdle, a marginal ring of small granules, very small pores covering the entire valve face and occasionally having internal valves. The new species is compared with all Angusticopula species known worldwide and with several Melosira species showing a similar combination of characters. Short notes on its ecology are included.